2018
DOI: 10.1016/j.cgh.2017.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Use of Biologic Therapy by Pregnant Women With Inflammatory Bowel Disease Does Not Affect Infant Response to Vaccines

Abstract: Vaccination of infants against HiB and tetanus toxin, based on antibody titers measured when infants were at least 7 months old, does not appear to be affected by in utero exposure to biologic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 24 publications
5
75
0
6
Order By: Relevance
“…It is generally recommended that live vaccines should not be given to infants exposed to biologic agents in utero for at least 6 months after birth, because of a theoretical concern about the response to vaccination. Although there are no published data following exposure to IL‐23p19 inhibitors, the Pregnancy in Inflammatory Bowel Disease and Neonatal Outcomes (PIANO) registry found use of other biologic therapies by pregnant women with inflammatory bowel disease did not affect infant response to Haemophilus influenzae B or tetanus vaccines . In adult patients, long‐term (≥3 years) treatment with ustekinumab was not found to compromise immune response to pneumococcal or tetanus vaccines, but there are no data on vaccine response during treatment with IL‐23p19 inhibitors .…”
Section: Unmet Needsmentioning
confidence: 99%
“…It is generally recommended that live vaccines should not be given to infants exposed to biologic agents in utero for at least 6 months after birth, because of a theoretical concern about the response to vaccination. Although there are no published data following exposure to IL‐23p19 inhibitors, the Pregnancy in Inflammatory Bowel Disease and Neonatal Outcomes (PIANO) registry found use of other biologic therapies by pregnant women with inflammatory bowel disease did not affect infant response to Haemophilus influenzae B or tetanus vaccines . In adult patients, long‐term (≥3 years) treatment with ustekinumab was not found to compromise immune response to pneumococcal or tetanus vaccines, but there are no data on vaccine response during treatment with IL‐23p19 inhibitors .…”
Section: Unmet Needsmentioning
confidence: 99%
“…There are no reports to evidence IFX-associated child immunodeficiencies or developmental disorders. Normal development of T and B cells, normal Ig concentrations and adequate vaccination responses have been observed [57, 58]. however, there is one case report on a fatal disseminated Bacillus Calmette-Guérin (BCG) infection in a child exposed to IFX in utero, who had received a tuberculosis vaccination [59].…”
Section: Biologics: Tnf-α Inhibitorsmentioning
confidence: 99%
“…A most recent study with children exposed to anti-TNF-α during pregnancy has indicated that responses to tetanus and Hemophilus influenzae  B vaccines were not affected and that T‑helper cell and B cell responses were to be assumed [58]. …”
Section: Biologics: Tnf-α Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations